PENGARUH PENYAJIAN LAPORAN KEUANGAN, AKSESIBILITAS LAPORAN KEUANGAN DAN PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Mawaddah Mawaddah; Murhaban Murhaban; Dewi Keumala Sari (LPPM STIE Lhokseumawe, 2019)
This study aims to examine the effect of the presentation of financial statements, the accessibility of financial statements and the application of the government's internal control system to the accountability of regional financial management at SKPD in Lhokseumawe. The data used in this study is primary data. The sample in this study consisted of 70 employees at 35 SKPD in Lhokseumawe. Data processing is done using multiple linear regression analysis. The results of the study that are: Partially, the presentation of financial statements has a significant effect on the accountability of regional financial management at SKPD in Lhokseumawe. Accessibility of financial statements has a significant effect on the accountability of regional financial management at SKPD in Lhokseumawe. The implementation of the government's internal control system has a significant effect on the accountability of regional financial management at SKPD in Lhokseumawe. Simultaneously, the presentation of financial statements, the accessibility of financial statements and the application of the government's internal control system have a significant effect on the accountability of regional financial management at SKPD in Lhokseumawe.